Novel Method of 3-Dimensional Graphical Representation for Proteins and Its Application. (11th June 2018) - Qi, Zhao-Hui; Li, Ke-Cheng; Ma, Jin-Long; Yao, Yu-Hua; Liu, Ling-Yun
In this article, we propose a 3-dimensional graphical representation of protein sequences based on 10 physicochemical properties of 20 amino acids and the BLOSUM62 matrix. It contains evolutionary information and provides intuitive visualization. To further analyze the similarity of proteins, we extract a specific vector from the graphical representation curve. The vector is used to calculate the similarity distance between 2 protein sequences. To prove the effectiveness of our approach, we apply it to 3 real data sets. The results are consistent with the known evolution fact and show that our method is effective in phylogenetic analysis.